Assessing the logistics cost of fisheries the case of fishers in Maasin, Sarangani Province - Cruz, Claire Estelle G. (2016)
The objectives of conducting this study is to analyze the logistics costs of the fishers from Maasim, Sarangani Province. Thus, using the data from the survey of the project ?Production Aspects of the Philippine Tuna Value Chain? which is funded by the Commission on Higher Education, key informant interviews and a focus group discussion to supplement the information of the researcher, the researcher analyzed the supply chain of fisheries in the area and identify the logistics cost structure of the fishers. Thus, the researcher identified five (5) types of logistics costs: Fuel, Ice, Water Labor and Port fees, while other logistics costs were not identified. Thus, fuel costs is reported to have the largest share in the logistics costs of fishers. This study also aims to identify the factors affecting the logistics costs of fishers. Hence, there four (4)factors assumed to be indicators of logistics costs of fishers: Participation in Organization, Boat Capacity, the type of Buyer they have, and the level of Government Support received by the fishers. Thus, comparative analyses were done to determine the determine the differences in the costs, performance and profitability of the fishers. Also, the researcher generated a linear regression model to further support this hypothesis including the marginal volume and price of the fishes as independent variables and presenting the relationship of the assumed indicators to the marginal logistics costs of fishers. Hence, the volume is considered the most significant indicator of logistics costs followed by the capacity of boat used. Thus, while participants in organization may have lower average logistics costs compared to nonparticipants, their participants may have actually increase their marginal logistics. Thus, they may only present lower costs since these fishers may already have low costs even before participating in organizations. Furthermore, fishers from the Maasim area are confronted with several issues and problems in their fishing and marketing. Hence, while some issues, such as storms, may be difficult to address, there other issues where the local government can actually intervene and provide support. The facilities in the area are yet to be improve, thus, replacing or enhancing these facilities may help in reducing the share of the costs in the sales, thereby creating larger profit shares of fishers.